2020
DOI: 10.4041/kjod.2020.50.5.324
|View full text |Cite
|
Sign up to set email alerts
|

Positional changes in the mandibular proximal segment after intraoral vertical ramus osteotomy: Surgery-first approach versus conventional approach

Abstract: Objective To compare postoperative positional changes in the mandibular proximal segment between the conventional orthognathic surgery (CS) and the surgery-first approach (SF) using intraoral vertical ramus osteotomy (IVRO) in patients with Class III malocclusion. Methods Thirty-eight patients with skeletal Class III malocclusion who underwent bimaxillary surgery were divided into two groups according to the use of preoperative orthodontic treatment CS group (n = 18) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…5 ). Our results are in line with the findings of a previous study by Jung et al, 21 who used lateral cephalometric analysis to compare the changes in the proximal segment of the mandible in patients treated with SFA and CA. They showed similar positional changes between the 2 groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…5 ). Our results are in line with the findings of a previous study by Jung et al, 21 who used lateral cephalometric analysis to compare the changes in the proximal segment of the mandible in patients treated with SFA and CA. They showed similar positional changes between the 2 groups.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, several previous studies have been performed to analyze the amount and direction of condylar displacement. 12,[17][18][19][20][21] Although efforts have been made to control the position of the proximal segment to ensure surgical stability, 15,22 these previous studies mostly assessed the condylar positional changes in two-dimensional (2D) radiographs such as lateral cephalograms and 2D reformatted images derived from the computed tomography (CT). Soverina et al, 9 in their systematic review, reported that because all articles described stability using a penultimate time point of "after surgery" and not "after debonding," orthodontic movements and consequent mandibular movements could have influenced cepha-lometric measurements.…”
mentioning
confidence: 99%
“…1 Condylar resorption (CR) is an uncommon but well-known clinical condition that can occur after surgical repositioning of the jaws. 2 , 3 It represents the advanced stage of condylar remodeling, irreversibly affecting the temporomandibular joint (TMJ). 3 - 5 As a result of mechanical load, the adaptive mechanisms that normally allow to balance bone resorption and bone formation on the condylar surface are completely lost, resulting in morphological alterations of the condylar structure.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Referring to orthognathic surgery, all osteotomies can lead to CR, which can occur in both mono-maxillary and bi-maxillary surgery. 2 , 12 Bilateral sagittal split osteotomy (BSSO) and/or Le Fort I osteotomy can modify the mechanical forces on the condylar surface, resulting in CR. 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation